Triclabendazole Induces Pyroptosis by Activating Caspase-3 to Cleave GSDME in Breast Cancer Cells - Yan, Liang; Liu, Yi; Ma, Xue-feng; Hou, Dan; Zhang, Yu-hui; Sun, Yong; Shi, Shan-shan; Forouzanfar, Tim; Lin, Hai-yan; Fan, Jun; Wu, Gang (Frontiers in Pharmacology, 2021)
Pyroptosis is a form of programmed cell death in which gasdermin E (GSDME) plays an important role in the cancer cell, which can be induced by activated caspase-3 on apoptotic stimulation. Triclabendazole is a new type of imidazole in fluke resistance and has been approved by FDA for the treatment of fascioliasis and its functions partially acting through apoptosis-related mechanisms. However, it remains unclear whether triclabendazole have obvious anticancer effects on breast cancer cells. In this study, to test the function of triclabendazole on breast cancer, we treated breast cancer cells with triclabendazole and found that triclabendazole induced lytic cell death in MCF-7 and MDA-MB-231, and the dying cells became swollen with evident large bubbles, a typical sign for pyroptosis. Triclabendazole activate apoptosis by regulating of the apoptoic proteins levels including bax, bcl-2 and enhanced cleavage of caspase-8/9/3/7 and PARP. In addition, enhanced cleavage of GSDME was also observed, which indicates the secondary necrosis/pyroptosis is further induced by active caspase-3. Consistent with this, triclabendazole-induced GSDME-N terminal fragment cleavage and pyroptosis were reduced by caspase-3 specific inhibitor (Ac-DEVD-CHO) treatment. Moreover, triclabendazole induced reactive oxygen species (ROS) elevation and increased JNK phosphorylation and lytic cell death, which could be rescued by ROS scavenger (NAC), suggesting that triclabendazole induce GSDME-dependent pyroptosis is related to ROS/JNK/Bax-mitochondrial apoptotic pathway. Besides, we showed that triclabendazole significantly reduced tumor volume by promoting the cleavage of caspase-3, PARP and GSDME in xenograft model. Altogether, our results revealed that triclabendazole induce GSDME-dependent pyroptosis by caspase-3 activation at least partly through augmenting ROS/JNK/Bax-mitochondrial apoptotic pathway, providing insights of this on-the-market drug in its potential new application in cancer treatment.